A case report of profound neonatal Jaundice due to bilateral adrenal hemorrhage - Y ZahedPasha (Babol University of Medical Sciences, 2002)
Background and Objective: Neonatal adrenal hemorrhage is frequently accompanied with large fetal size and fetal hypoxia. The incidence of this disease is 1.7-1.9 per 1000 births, with a variety of clinical manifestations such as abdominal mass, jaundice and hypotension. The aim of this report was to present a case with profound neonatal jaundice with bilateral adrenal hemorrhage which rarely occurs. Case: A male newborn with a birth weight of 3900gr and gestational age of 36-38 weeks was born by normal vaginal deliver (NVD). He was big for gestational age neonate and developed to profound jaundice and bilateral adrenal hemorrhage, which required exchange transfusion for six times. Conclusion: Adrenal hemorrhage should be considered in profound neonatal jaundice with unknown etiology.